Pengelolaan Pembiayaan Pendidikan di Sekolah Menengah Pertama Swasta - Fatmawati, Siti; Nugraha, Mulyawan Safwandy (Epistemic: Jurnal Ilmiah Pendidikan, 2024)
This study aims to explore the management of educational financing at SMP Islam Bakti Asih, where efficient financial management is key to achieving educational goals. The research is motivated by the financial challenges faced by private schools due to limited resources, affecting the quality of education and the welfare of teaching staff. Using a qualitative phenomenological approach, data were collected through observations, in-depth interviews, and documentation on budget planning, fund utilization, and financial oversight. The key findings indicate that the primary sources of funding come from the foundation and government (BOS) funds, which are utilized through detailed budget planning and regular financial audits to ensure transparency and accountability. The implications of these findings highlight the importance of comprehensive and proactive financial management, not only to maintain the school's financial stability but also to enhance the quality of education provided. This study contributes to the literature on educational financial management by providing insights into best practices for managing funds in private schools. Additionally, the limitations of this study include its narrow focus on a single school and the limited number of respondents, which opens opportunities for further research in broader contexts.